KAJIAN YURIDIS TENTANG KEWENANGAN MENTERI DALAM NEGERI MENGAWASI DAN MEMBATALKAN QANUN ACEH - Suhardi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2016)
This research aimed to investigate the extent of the central government through Minister of Home Affairs in supervising and cancelling the Aceh Qanun as well as examining its supervision and cancellation mechanism as the regional legalisation product that has privilege and speciality. The result indicated that the supervision and cancellation of Aceh Qanun conducted by the government through the Ministry of Home Affairs had a legal error. Because the Aceh Qanun was a cooperative legalisation product of the regional executive and legislative, the cancellation should be conducted cooperatively by the regional executive and legislative, (not by the central government only). The legal instrument of Aceh Qanun cancellation was the President Regulations. The mechanism of Aceh Qanun supervision and cancellation conducted by the government was only for those related to general governance. However, for the Qanun related to the privilege and specific life of Aceh community, for example, the Islamic law Qanun, the supervision and cancellation are carried out by the judicial review of the high court. Abstrak: Tulisan ini bertujuan untuk melihat sejauh mana kewenangan pemerintah pusat melalui Menteri Dalam Negeri dalam mengawasi dan membatalkan Qanun Aceh dan bagaimana mekanisme pengawasan dan pembatalan Qanun Aceh sebagai produk hukum daerah yang memiliki keistimewaan dan kekhususan. Dari hasil telaahan lebih lanjut diketahui bahwa pengawasan dan pembatalan Qanun Aceh yang dilakukan oleh pemerintah melalui Mendagri merupakan kekeliruan hukum. Hal ini dikarenakan Qanun Aceh adalah hasil produk hukum bersama eksekutif dan legislatif daerah dan sudah seharusnya pembatalan dilakukan bersama eksekutif dan legislatif tingkat daerah, bukan dilakukan oleh pemerintah pusat sebagai lembaga eksekutif sepihak. Instrumen hukum yang digunakan untuk pembatalan Qanun Aceh adalah Peraturan Presiden. Untuk Qanun Aceh, mekanisme pengawasan oleh pemerintah hanyalah qanun yang berkaitan dengan tata kelola pemerintah pada umumnya, sedangkan Qanun Aceh yang berkaitan dengan kehidupan masyarakat Aceh yang bersifat khusus dan istimewa seperti Qanun Syariat Islam, pengawasan dan pembatalan dilakukan melalui judicial review oleh Mahkamah Agung. Kata Kunci: Kajian Yuridis, KEMENDAGRI, Qanun Aceh